Stable expression ratios of five pyroptosis-inducing cytokines in the spleen and thymus of mice showed potential immune regulation at the organ level. (March 2020) - Fan, H; Zhang, S; Li, N; Fan, P; Hu, X; Liang, K; Cheng, X; Wu, Y
Background: The immune system is one of the most complex regulatory systems in the body and is essential for the maintenance of homeostasis. Despite recent breakthroughs in immunology, the regulation of the immune system and the etiology of autoimmune diseases such as lupus remain unclear. Systemic lupus erythematosus is a systemic autoimmune disease with abnormally and inconsistently expressed pro-inflammatory cytokines. Pyroptosis is a pro-inflammatory form of programmed cell death that is associated with systemic lupus erythematosus. The thymus and spleen are important immune organs involved in systemic lupus erythematosus. Therefore, this study investigated the difference in expression of pyroptosis-inducing pro-inflammatory cytokines between the spleen and thymus in lupus model mice and in control mice, to describe immune regulation at the organ level. Objective: To investigate differences in the expression of pyroptosis-inducing cytokines in the spleen and thymus and to explore immune regulatory networks at the organ level. Methods: Two groups of lupus mice and two groups of control mice were utilized for this study. Using the thymus and spleen of experimental animals, mRNA expression levels of five pyroptosis-inducing cytokines (interleukin 1β, interleukin 18, NLRP3, caspase-1 and TNF-α) were determined via quantitative polymerase chain reaction. In addition, tissue distribution of these cytokines was investigated via immunohistochemistry. Results: All five pyroptosis-inducing inflammatory cytokines showed higher expression in the spleen than in the thymus ( p  < 0.05). Moreover, the spleen/thymus expression ratios of all five pyroptosis-inducing cytokines were not statistically different between the four experimental groups. Expression of all five cytokines exhibited a stable ratio (spleen/thymus ratios). This distinctive stable spleen/thymus ratio was consistent in all four experimental groups. The stable spleen/thymus ratios of the five inflammatory cytokines were as follows: interleukin 1β (2.02 ± 0.9), interleukin 18 (2.07 ± 1.06), caspase-1 (1.93 ± 0.66), NLRP3 (3.14 ± 1.61) and TNF-α (3.16 ± 1.36). Immunohistochemical analysis showed the cytokines were mainly expressed in the red pulp region of the spleen and the medullary region of the thymus, where immune-activated cells aggregated. Conclusion: The stable spleen/thymus expression ratios of pyroptosis-inducing cytokines indicated that immune organs exhibit strictly regulated functions to maintain immune homeostasis and adapt to the environment.